Ultrastructural Changes in the Rogor Induced Toxicity and its Antidote on the Liver of Mice - Prasad, Archana; Verma, Ashmi (Tribhuvan University Journal, 2013)
Pesticides such as Rogor, Endosulfan, DDT, Daminozole etc. are commonly used to meet the enormous demand of fodder crops. These exert adverse effects at both biochemical and cellular level. They cause several chronic diseases like skin diseases, cancer, liver problems, neural and hormonal diseases. Gross symptoms of damages are seen in very late stages. Thus, present investigation was undertaken to evaluate ultrastructural changes under Scanning Electron Microscope (SEM).Mice exposed to 2 ppm Rogor for 7 days and 14 days showed behavioural changes temporarily. Ultrastructural observation showed cellular alterations and various damage like blabbing, protuberances, ruffling, lobopodia. Serum SGPT was more in 2 ppm Rogor than those in 2 ppm Rogor along with 3 ppm Selenium treated mice. Selenium treated liver of mice showed striking results with the reduction in toxicities as they are found in 2 ppm Rogor treated liver cells.